The coordinate of point L' after translation is L'(6, -8)
Given the coordinates of JKLM as J(-7,-2), K(-4,-2), L(-2,-5) and M(-9,-5)
Using the translation rule
(x, y) → (x + 8, y − 3)
The coordinate of point L' after translaton will be;
L' = (-2+8, -5-3)
L' = (6, -8)
Hence the coordinate of point L' after translation is L'(6, -8)
Learn more on translation here: brainly.com/question/12861087
b. The rise is –4, the run is –5.
c. The run is –5, the rise is 4.
d. The run is 4, the rise is 5.
Answer: a. The rise is –5, the run is 4.
Step-by-step explanation:
Given :- A line in the Cartesian plane passes through the points (–2, 4) and (2, –1)
Let and
We know that rise of a line = vertical change of points=change in the coordinates of y
=
Run of line=horizontal change of points=change in the coordinates of x
=
Therefore, The rise is –5, the run is 4.
B.15
C.45
D.30
I really need help.
The width of the rectangle is 30 units.
To find the width of a rectangle, we need to use the formula for the perimeter of a rectangle, which is 2(length + width). In this case, we are given the perimeter as 90 and the length as 15. Plugging these values into the formula, we get: 90 = 2(15 + width).
Now we can solve for the width. First, simplify the equation: 90 = 30 + 2(width).
Then, subtract 30 from both sides: 60 = 2(width). Divide both sides by 2 to isolate the width: width = 30.
Therefore, the width of the rectangle is 30 units.
#SPJ2
Answer
x ≥ 68
Explanation
let that number be x.
(3/4) of x = (3/4) × x
= 3x/4
Decrease 3x/4 by 9,
3x/4 - 9
This expression is at least 42,
∴ 3x/4 - 9 ≥ 42
3x - 36 ≥ 168
3x ≥ 168 + 36
3x ≥ 204
x ≥ 68
Answer:
2n(n + 5)(n + 6)
Step-by-step explanation:
given the expression
2n³ + 22n² + 60n ← factor out the common factor of 2n from each term
= 2n(n² + 11n + 30) ← factorise the quadratic
consider the factors of the constant term (+ 30) which sum to give the coefficient of the n- term (+ 11)
the factors are + 5 and + 6 , since
+ 5 × + 6 = + 30 and 5 + 6 = + 11
use these factors to split the n- term
n² + 5n + 6n + 30 ( factor the first/second and third/fourth terms )
= n(n + 5) + 6(n + 5) ← factor out (n + 5) from each term
= (n + 5)(n + 6)
Then
2n³ + 22n² + 60n
= 2n(n + 5)(n + 6) ← in factored form
Answer:
= -2b is the answer
Step-by-step explanation:
here we can see that we can cancel common terms from both numerator and denominator . 12 is divided by 6 we get 2 and x ,a and y are cancelled from the denominator .Only b is left in the numerator .
so final answer is -2b.